If your expression means:
f(x) = log ( 3 x )
then
f(1/3) = log ( 3 ∙ 1 / 9 ) = log ( 3 / 9 ) = log ( 1 / 3 ) = - log ( 3 )
_______
Remark:
log ( 1 ) = 0
log ( 1 / n ) = log ( 1 ) - log ( n ) = 0 - log n = - log ( n)
that's why
log ( 1 / 3 ) = - log ( 3 )
_______
If f(x)=log3x, what if f(1/9)?
3 answers
My typo.
f(1/9) = log ( 3 ∙ 1 / 9 ) = log ( 3 / 9 ) = log ( 1 / 3 ) = - log ( 3 )
f(1/9) = log ( 3 ∙ 1 / 9 ) = log ( 3 / 9 ) = log ( 1 / 3 ) = - log ( 3 )
If you mean log base 3, f(x) = log_3(x), then
f(1/9) = -2, since 1/9 = 3^-2
f(1/9) = -2, since 1/9 = 3^-2